Pengaruh Edukasi Kesehatan Berbasis Budaya Nggempe terhadap Pengetahuan Calon Pengantin tentang Persiapan Kehamilan Sehat Melalui Layanan Homecare - Wahyuningsi, Sri; Saudia, Baiq Eka Putri; Hanafi, Fachrudi (Bima Nursing Journal, 2025)
Maternal Mortality Rate,Infant Mortality Rate and stunting are still the main problems in improving health indicators, especially in Indonesia. In Kota Bima, the incidence of pregnant women with complications still exceeds the target rate of 20%, namely 36.41%. These problems can start from the pre-conception period. Bride and groom are a strategic target group in efforts to improve pre-conception health. This of course can pose various kinds of risks such as disease transmission, high-risk pregnancies and even maternal and infant mortality. By taking advantage of the cultural momentum leading up to the wedding, namely the "nggempe" culture where the bride and groom limit activities outside the home, health workers, especially midwives, can provide premarital reproductive health care, education and counseling as preparation for having a healthy pregnancy for the bride and groom during the "nggempe" period, at home. prospective bride and groom in homecare services with more educational time. During the "Nggempe" period, when the bride and groom can focus more on preparing for their wedding, it is hoped that they will receive maximum information about preparing for a healthy pregnancy. For this reason, researchers are very interested in conducting research on the effect of nggempe culture-based health education on the knowledge of prospective brides about preparing for a healthy pregnancy in Bima City. To determine the effect of nggempe culture-based health education on the knowledge of prospective brides about preparing for a healthy pregnancy through homecare services in the city of Bima. The research method used the Quasy Experimental One Group Pretest Posttest Design. The research was conducted in April - June 2023. The population for this study were all prospective brides and grooms who had registered at the KUA Kota Bima with a sample using a minimum sample of 30 people who met the inclusion and exclusion criteria. Data collection using a questioner. Data analysis used Univariate analysis and Bivariate analysis by carrying out the normality test. after analyzing the data, the average value of knowledge before being given health education was 62.22 (enough category), while after being given an intervention in the form of culture-based health education in homecare services, the value of knowledge increased with an average of 93.32 ( good category). The statistical test results obtained a p-value of 0.000 <Î± = 0.05. There is an influence of nggempe culture-based health education on the knowledge of prospective brides about preparing for a healthy pregnancy through homecare services in the city of Bima